2022
DOI: 10.3390/microorganisms10010169
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Beta-Hydroxy-Beta-Methyl Butyrate Supplementation Inhibits Hepatic Fat Deposition via Regulating Gut Microbiota in Broiler Chickens

Abstract: The present study is aimed to explore the effects of different dietary beta-hydroxy-beta-methyl butyrate (HMB) levels (0, 0.05%, 0.10%, or 0.15%) on liver lipid metabolism on Wenshi broiler chickens. Results showed that HMB reduced the liver weight as well as liver concentrations of triacylglycerol (TG) and total cholesterol (TC) (quadratically, p < 0.05), and the lowest values were observed in the 0.10% HMB group. Meanwhile, HMB supplementation significantly altered the expression levels of key genes relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…An interesting finding from the present study was that crude lipid content in shrimp muscle significantly decreased in response to dietary HMB supplementation, which may partially contribute to the improved muscle firmness of the HMB2 group. Previous studies reported that dietary HMB could decrease fat deposition in Bama Xiang mini-pigs [ 63 ] and broiler chickens [ 64 ] through regulating the Bacteroidetes -acetic acid-AMPK α axis and gut microbiota respectively, which needs to be further investigated and verified in aquatic animals.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding from the present study was that crude lipid content in shrimp muscle significantly decreased in response to dietary HMB supplementation, which may partially contribute to the improved muscle firmness of the HMB2 group. Previous studies reported that dietary HMB could decrease fat deposition in Bama Xiang mini-pigs [ 63 ] and broiler chickens [ 64 ] through regulating the Bacteroidetes -acetic acid-AMPK α axis and gut microbiota respectively, which needs to be further investigated and verified in aquatic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is urgent to seek drugs or feed additives to improve fat metabolism in laying hens. While HMB, a metabolite of L-leucine in the liver, was recently reported to modulate hepatic lipid metabolism in broiler chickens [ 22 ], it is still unknown whether dietary supplementation with HMB could alleviate fat over-accumulation in laying hens. This is because there are huge differences between broiler chickens and layer chickens in terms of genetics, nutrition, physiology, and feeding management [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frankly, this is an expected finding because the gut microbiota is well-known for its broad range of roles in the regulation of many physiological and pathological processes, particularly metabolism [ 46 ]. In addition, studies in mice and broilers have already indicated that the gut microbiota plays a role in the lipid-lowering action of HMB [ 20 , 22 ]. However, until now, it has been unclear how HMB shapes the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations